Pengaruh Book Tax Differences terhadap Pertumbuhan Laba pada Perusahaan Sektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Tahun 2021–2024 - Denadia Nita Sarani; Mohammad Hatta Fahamsyah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to examine the effect of Book Tax Differences on earnings growth in food and beverage companies listed on the Bursa Efek Indonesia during the 2021–2024 period. The independent variables consist of Permanent Differences (PPBTD), Temporary Differences (PTBTD), Large Positive Book-Tax Differences (LPBTD), and Large Negative Book-Tax Differences (LNBTD), while earnings growth serves as the dependent variable. PPBTD is measured by the ratio of total permanent differences to total assets, PTBTD by the ratio of total temporary differences to total assets, and LPBTD and LNBTD are classified using the top and bottom 20 percent quantiles, respectively. Earnings growth is calculated based on the change in net income from the previous year. The sample comprises 44 companies, resulting in 176 firm-year observations over four years. The findings indicate that PPBTD and PTBTD do not have a statistically significant effect on earnings growth. In contrast, LPBTD and LNBTD exhibit a significant negative effect on earnings growth. Furthermore, LNBTD demonstrates the strongest and most dominant negative influence. These results suggest that substantial discrepancies between accounting income and taxable income, particularly large negative differences, may signal a decline in firms’ earnings performance.